How have the size and shape of the UK state changed? - Bee Boileau; Isabel Stockton; Ben Zaranko (Institute for Fiscal Studies (IFS), 2024)
We describe how the size and shape of the state have changed since the mid 1950s and over the 2019-24 parliament, and discuss the future outlook.
Keywords: 330; Government finances and spending; COVID-19; Government spending; Pensioner benefits; Public finance; State pensions; Trends; Working age benefits